INTERAKSI PARASOSIAL PENGGEMAR K-POP DI MEDIA SOSIAL (Studi Kualitatif pada Fandom Army di Twitter) - Eka Putri Wardani; Rina Sari Kusuma (Bricolage : Jurnal Magister Ilmu Komunikasi, 2021)
In Indonesia, the Korean wave (Hallyu) has become the most popular phenomenon in the past few years. One of the products from Hallyu is Korean pop music or also known as K-pop. The development of K-pop in Indonesia grows rapidly through the internet and social media that easy to access. The convenience offered by social media makes fans feel close to their idols. This study tries to analyze the phenomenon of fan behavior on social media towards their idols, where their media behavior leads to parasocial interactions. Parasocial interactions can be defined as the extent to which fans interact psychologically with media characters. Therefore, the purpose of this study is to see how the process of parasocial interaction and media activities carried out by Army on Twitter social media through their psychological response occurs in this study. The result of this study then analyzed using PSI-Process Scale categorization. This study used a qualitative methodology and collect data through interviews and observations. The results showed that all informants actively interacted with BTS through social media Twitter, where the parasocial interaction involved the informants' psychological responses. All of the informants give cognitive responses, affective responses, and behavioral responses when carrying out their parasocial interactions.Keywords: Fandom, parasocial interaction, K-Pop, social media.